2020
DOI: 10.1136/bmjsem-2020-000791
|View full text |Cite
|
Sign up to set email alerts
|

Systematic development of an injury prevention programme for judo athletes: the IPPON intervention

Abstract: ObjectivesTo systematically develop an injury prevention programme in judo and test its feasibility: Injury Prevention and Performance Optimization Netherlands (IPPON) intervention.MethodsWe used the five-step Knowledge Transfer Scheme (KTS) guidelines. In the first two steps, we described the injury problem in judo and showed possibilities to reduce the injury rates. In the third step, the Knowledge Transfer Group (KTG) translated this information into actions in judo practice. Expert meetings and practical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Recently it was reported that the isokinetically measured DCR (dynamic control ratio) ratio with the eccentric Hamstrings strength could also help in the early identification of vulnerable judokas and help in optimal conditioning of judokas ( Šimenko, Karpljuk & Hadžić, 2022 ). Also, raising awareness with the regular implementation of already available exercise prevention programs developed especially for judo ( Akoto et al, 2018 ; Malliaropoulos et al, 2019 ; von Gerhardt et al, 2020 ) would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was reported that the isokinetically measured DCR (dynamic control ratio) ratio with the eccentric Hamstrings strength could also help in the early identification of vulnerable judokas and help in optimal conditioning of judokas ( Šimenko, Karpljuk & Hadžić, 2022 ). Also, raising awareness with the regular implementation of already available exercise prevention programs developed especially for judo ( Akoto et al, 2018 ; Malliaropoulos et al, 2019 ; von Gerhardt et al, 2020 ) would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…The ACL is also the most serious knee injury in judo [ 48 ]. Therefore, suggestions have been made for the importance of developing an exercise prevention programme for judo [ 48 , 49 , 50 ]. Combined with the injury preventive programmes, the DCR ratio with the eccentric H strength could also help in the early identification of vulnerable judokas and optimal conditioning of judo athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The IPPON intervention is an injury prevention programme designed specifically to reduce injuries in judo athletes. 16 The KTS 15 was used for the systematic development of the programme. The five steps of the bottom-up development process have been described in full detail before 16 and summarised in online supplemental appendix E. The intervention was available through instructional videos, 18 and an instruction book with photos and explanation of all exercises including key points of correct performance of the exercises.…”
Section: Interventionmentioning
confidence: 99%
“…16 The KTS 15 was used for the systematic development of the programme. The five steps of the bottom-up development process have been described in full detail before 16 and summarised in online supplemental appendix E. The intervention was available through instructional videos, 18 and an instruction book with photos and explanation of all exercises including key points of correct performance of the exercises. There were also hand-held photo cards with descriptions for the trainers to use on the tatami (judo training ground).…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation